Murattal Therapy Reduces the Anxiety of Patients Treated in the Intensive Care Unit of a Hospital - Rachmah, Siti; Mawaddah, Nurul; Jayanti, Titin Dwi (Al-Hijrah Indonesia, 2024)
Patients treated in the Intensive Care Unit (ICU) can experience anxiety due to the conditions they experience and the care environment. Untreated anxiety can affect physiological changes or the patient's hemodynamic status, resulting in worsening conditions. Nursing interventions based on Indonesian nursing intervention standards (SIKI) using murattal therapy can be used to overcome patient anxiety. The purpose of this study was to determine the effect of murattal therapy on patient anxiety in the ICU of Aisyiyah Siti Fatimah Hospital Tulangan Sidoarjo. The research method used a Pre-Experiment design with a one group pretest-posttest design. The study population was all patients treated in the ICU. The sampling technique was carried out using the Purposive Sampling technique, obtaining a sample of 48 patients who met the inclusion and exclusion criteria. Data collection used an anxiety level instrument in accordance with the Standar Luaran Keperawatan Indonesia (SLKI). While the murattal therapy intervention is given in accordance with the Indonesian nursing intervention standards (SIKI) which are given in the form of MP3 audio of the letter ar-rahman. The results of the study showed a decrease in anxiety scores by 39 points after being given murattal therapy intervention. The results of the paired T-test obtained a p value of 0.000, this indicates that there is an effect of murratal therapy on the anxiety of patients treated in the ICU. Murattal therapy intervention can be used as a non-pharmacological intervention in overcoming anxiety problems.